Multicultural Society Reflected in Freedom Writers Movie: Sociolinguistics Approach - Keiza, Zakia Nurin (International Journal of Language and Literature, 2023)
Sociolinguistics analysis of “Freedom Writer” movie is an analysis of the variation of language that used in society and cultural. The research objective is to analyze the differences in language styles used by multicultural society as well as to determine their relationship with the level of education and cultural backgrounds. The data source in this research is The Freedom Writers movie by Richard La Gravenese, while the data in this research are spoken dialogue that contains in the level of word pronunciation, vocabulary selection, and language errors. This research used a descriptive qualitative method. The data analysis will be in the form of observations on each selected utterance, followed by presenting the data and drawing a conclusion. The findings reveal that various groups of individuals employ different languages depending on their social standing. Some reasons contribute to these disparities. Besides from race, education level and social background are important elements in the development of a person's language patterns.